2018
DOI: 10.13004/kjnt.2018.14.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Paraplegia Following Spinal Cord Contusion from an Indirect Gunshot Injury

Abstract: Spinal cord injuries are debilitating and life threatening. Paraplegia due to direct traumatic gunshot injury to the spinal cord is common. The most common cause of spinal cord injury is road traffic accidents. This is followed by spinal cord injury due to a fall from a height. Most of the spinal cord injuries due to gunshot wounds occur as a result of direct traumatic effects. We present a rare case of a 49-year-old male with trauma. He developed paraplegia after a gunshot wound injury to the neck and contusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…SCI is a neurological disorder resulting in motor dysfunction even permanent paralysis, which not only difficult to treat but also expensive to rehabilitation therapy [2]. In the most instances, SCI is mainly caused by physical traumas, such as traffic accidents, falls, assaults and sport injuries [3,4]. Nevertheless, several nontraumatic diseases, such as insufficient blood flow, tumor and inflammatory injury can also induce the occurrence of SCI [5].…”
Section: Introductionmentioning
confidence: 99%
“…SCI is a neurological disorder resulting in motor dysfunction even permanent paralysis, which not only difficult to treat but also expensive to rehabilitation therapy [2]. In the most instances, SCI is mainly caused by physical traumas, such as traffic accidents, falls, assaults and sport injuries [3,4]. Nevertheless, several nontraumatic diseases, such as insufficient blood flow, tumor and inflammatory injury can also induce the occurrence of SCI [5].…”
Section: Introductionmentioning
confidence: 99%
“…Patil et al [2] reported a case of paraplegia with complete loss of sensation below D10 level as a result of GSW causing spinal cord injury without bony injuries and violation of spinal axis. A similar case of conservative management has been reported by Khan et al [16], who showed contusion to the spinal cord, without direct trauma, in a patient with complete paraplegia after a GSW injury in the T1-T2 region.…”
Section: Discussionsupporting
confidence: 76%
“…GSW-induced spinal injury yields a range of different outcomes, depending on various mechanical and biological factors [2]. Most frequently the spinal cord sustains a direct trauma, such as contusion, transection, vascular lesion and ischemia, that can be associated with damage of surrounding bones and soft tissues; thus, available data largely regard the conservative management of patients who survived to GSW to the spine with subsequent contusion of spinal cord [15,16]. Studies regarding the pathogenesis of GSW to the spine also focus on functional and radiological aspects of the lesion in order to guide surgical and therapeutical decision-making in the specific neurological cases [1,2,18,19].…”
Section: Discussionmentioning
confidence: 99%